2017
DOI: 10.1590/1678-457x.27216
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Pleurotus pulmonarius mushroom grown on maize stalk residues supplemented with various levels of maize flour and wheat bran

Abstract: The use of supplemented agricultural waste in mushroom cultivation can be one of the environmentally friendly strategies for poverty alleviation. The study evaluated the performance of Pleurotus pulmonarius mushroom grown on maize stalk supplemented with varying levels of wheat bran (WB) and maize flour (MF). A completely random design was used for the experiments. It was observed that Pleurotus pulmonarius was significantly affected by varying levels of supplementation, as 20% WB supplementation encountered h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
6
1
Order By: Relevance
“…P. pulmonarius reached a yield of 13.78%, which is slightly higher than those reported by [25] on maize stalk supplemented with maize flour residues (11%). The yield of P. djamor (13.36%) was slightly lower than the reported value [26] who obtained 156 g of fruit bodies in 750g of sugarcane bagasse-based substrate, which would be equivalent to a yield of 20.8%, while [27] reported 4.68% in the same substrate.…”
Section: St Experimentscontrasting
confidence: 62%
“…P. pulmonarius reached a yield of 13.78%, which is slightly higher than those reported by [25] on maize stalk supplemented with maize flour residues (11%). The yield of P. djamor (13.36%) was slightly lower than the reported value [26] who obtained 156 g of fruit bodies in 750g of sugarcane bagasse-based substrate, which would be equivalent to a yield of 20.8%, while [27] reported 4.68% in the same substrate.…”
Section: St Experimentscontrasting
confidence: 62%
“…Rapid mycelial colonization is known to decrease contamination losses significantly, reducing the incubation time and productive period in an edible mushroom production system [35]. Under in vitro conditions, by controlling the temperature, humidity, and nutrient medium, the mycelial growth allows the evaluation of the vigor and growth speed of isolated strains.…”
Section: Discussionmentioning
confidence: 99%
“…Other methodologies for evaluating mycelial growth in the substrate were carried out by Bernardi et al [37], marking equidistant lines in the length of the flask with substrates. Alternatively, Thongklang [44] measured the linear length of the mycelium in bottles, while Mkhize et al [35] monitored growth in four equally spaced areas around the substrate bag. The disadvantage of our method, compared to other research, is that it would not be recommended to identify the stages of mycelial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also reported by Dewi (5). Agus et al (1), Fadjari (7) and Mkhize et al (17) reported that sawdust consists of 33-38% of cellulose, 15-25% of hemicellulose, and 18-33% of lignin. However, filter cake consist of carbon (26.51%), nitrogen (1.04 %), C/N (25.62), phosphate (6.142%), potassium (0.485 %), sodium (0.082%) calcium (5.785%), magnesium (0.419%), iron (0.191%) and mangan (0.115%).…”
Section: Mycelial Growth Covered the Substrat/baglog (Cm)mentioning
confidence: 99%
“…Winarni and Rahayu (20), reported that digested carbohydrate by fungal enzymes provide nutrients in the culture medium. Mkhize et al (17) observed that mycelial growth and short period mycelial colonization of Pleurotus ostreatus occurred with high concentration of maize flour and wheat bran. Due to its growth, the mycelia of oyster mushroom cover all the substrates in the baglog.…”
Section: Mycelial Growth Covered the Substrat/baglog (Cm)mentioning
confidence: 99%